Altered plasma metabolites and inflammatory networks in HIV-1 infected patients with different immunological responses after long-term antiretroviral therapy - Lu, Lianfeng; Yang, Yang; Yang, Zhangong; Wu, Yuanni; Liu, Xiaosheng; Li, Xiaodi; Chen, Ling; Han, Yang; Song, Xiaojing; Kong, Ziqing; Cao, Wei; Li, Taisheng (Frontiers in Immunology, 2023)
Background: Chronic metabolic changes relevant to human immunodeficiency virus type 1 (HIV-1) infection and in response to antiretroviral therapy (ART) remain undetermined. Moreover, links between metabolic dysfunction caused by HIV and immunological inflammation in long-term treated individuals have been poorly studied.: Untargeted metabolomics and inflammatory cytokine levels were assessed in 5047 HIV-infected individuals including 225 immunological responders (IRs) and 25 non-responders (INRs) before and after ART. The IRs and INRs were matched by age, gender, baseline viral load and baseline CD4+T cell counts. Another 25 agematched uninfected healthy individuals were also included as controls.Results: Among the 770 plasma compounds detected in the current study, significant changes were identified in lipids, nucleotides, and biogenic amino acids between HIVinfected patients and healthy controls. Principal Component Analysis (PCA) and Random Forest (RF) model suggested that levels of selected metabolites could differentiate HIV infected patients clearly from healthy controls. However, the metabolites profile identified in our patients were similar and only three metabolites including maltotetraose, N,NN, N-dimethyl-5-aminovalerate and decadienedioic acid (C10:2-DC) were different between IRs and INRs following long-term ART. The pathway enrichment analysis results revealed that disturbances in pyrimidine metabolism, 、sphingolipid metabolism and purine metabolism after HIV infection and these changes did not recover to normal levels in healthy controls even with suppressive ART. Correlation analysis of the metabolism-immune network indicated that interleukin (IL)-10, D-dimer, vascular cell adhesion molecule-1 (VCAM-1), intercellular cell adhesion molecule-1 (ICAM-1) and TNF-RII were positively correlated with most of the significantly changed lipid and amino acid metabolites, but negatively correlated with metabolites in nucleotide metabolism.Conclusions: Significant changes of many metabolites were observed in HIV-infected individuals before and after ART, regardless of their immunological recovery status.The disturbed metabolic profiles of lipids and nucleotides in HIV infection did not recover to the normal levels even after long-term ART. These changes are correlated with modified cytokines and biomarkers of chronic non-AIDS events, warranting try out of interventions other than ART.